Using mobile media creation to structure museum interpretation with professional vision - Muñoz Civantos, Angeles; Brown, Michael; Coughlan, Tim; Ainsworth, Shaaron E.; Lorenz, Katharina (Springer, 2016)
Mobile technology plays an increasing role in museum and cultural heritage contexts. In most cases, these tools support the relatively passive consumption of expert interpretations, or the unguided generation of content by users. This paper explores the potential for technologies to help museum visitors, encountering unfamiliar objects, to engage with them as a skilled professional interpreter would, through structured mobile experiences that focus on creating multimedia content. We explore this concept in the area of artefact interpretation and specifically how to enact a structured process of interpretation, as would commonly be taught in courses dedicated to the analytical diagnostics of visual evidence, such as Classical Archaeology or Art History. We discuss two field trials of prototype systems through which the structured creation of multimedia forms a basis for learning to interpret historical artefacts conducted in contexts of both formal and informal learning. By describing, implementing, and evaluating this approach, we contribute understanding of a new way to conceptualise active engagement in museum contexts, through the effective use of scaffolding and user generation of multimedia. We identify issues around the properties and flexibilities of multiple media for this purpose, links between provision for procedural and factual learning, and the value of media creation-based structures in improving the skills and confidence to interpret.